Stay woles and you are great! : Sadar diri yuk, biar keren.../ @qulkhairan ; editor, Hariyanto, Rusdianto dan Aya Sophia - @QULKHAIRAN; Hariyanto; Rusdianto; Aya Sophia (Diva Press, 2014)
170 hlm. ; 19 cm